PERANCANGAN ANIMASI PENDEK SEBAGAI SARAN KAMPANYE STOP BUANG ANJING DI DENPASAR - Boy Nugraha , I Made; Ananta Kusuma Putra, Gede Lingga (Kartala, 2022)
The number of stray dogs in Bali, especially in Denpasar not be separated from the role of the community itself, with the actions of the waste pet dog. Problems will occur if the behavior dispose of these dogs continue to be, the emergence of violence against dogs as well as a variety of viruses, so it is necessary to do an attempt at one of them with the design of a short animation as a means of campaign Stop Wasting Dogs in Denpasar, the goal is to provide education and information to change the mindset of people as well as to instill commitment in keeping a dog. in the process of designing animation theory that is in use in designing the animated short that is the theory of the twelve principles of animation theory and the design principles used in the design of the supporting medium. The research method used is observation method, interview method, the method of literature and methods of the study of the internet. “Attractive” as a concept in the design of a campaign Stop Wasting Dogs in Denpasar through the medium of the animated short, x banner,poster,t-shirt, totebag, booth 3D design,standing characters, content challenge Instagram instastory, stickers, youtube content thus expected to press the case of neglect of a dog that case throw pet dog does not occur again in the people of the city of Denpasar.